Vγ4+ T Cells: A Novel IL-17-Producing γδ T Subsets during the Early Phase of Chlamydial Airway Infection in Mice - Li-da Sun; Sai Qiao; Yue Wang; Gao-ju Pang; Xiao-yu Zha; Teng-Li Liu; Hui-Li Zhao; Ju-You Liang; Ning-bo Zheng; Lu Tan; Hong Zhang; Hong Bai (Mediators of Inflammation)
Our previous studies showed that γδ T cells provided immune protection against Chlamydial muridarum (Cm), an obligate intracellular strain of chlamydia trachomatis, lung infection by producing abundant IL-17. In this study, we investigated the proliferation and activation of lung γδ T cell subsets, specifically the IL-17 and IFNγ production by them following Cm lung infection. Our results found that five γδ T cell subsets, Vγ1+ T, Vγ2+ T, Vγ4+ T, Vγ5+ T, and Vγ6+ T, expressed in lungs of naïve mice, while Cm lung infection mainly induced the proliferation and activation of Vγ4+ T cells at day 3 p.i., following Vγ1+ T cells at day 7 p.i. Cytokine detection showed that Cm lung infection induced IFNγ secretion firstly by Vγ4+ T cells at very early stage (day 3) and changed to Vγ1+ T cells at midstage (day 7). Furthermore, Vγ4+ T cell is the main γδ T cell subset that secretes IL-17 at the very early stage of Cm lung infection and Vγ1+ T cell did not secrete IL-17 during the infection. These findings provide in vivo evidence that Vγ4+T cells are the major IL-17 and IFNγ-producing γδ T cell subsets at the early period of Cm lung infection.